1998
DOI: 10.1159/000014548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amphetamine and Phenylethylamine on Catecholamine Release in the Glomerular Layer of the Rat Olfactory Bulb

Abstract: In the present work, we have shown electrochemically that in the rat olfactory bulb (OB), extracellular dopamine (DA) was highest in the glomerular layer (GL), whereas extracellular noradrenaline (NA) appeared to be more uniformly distributed across layers. The GL catecholamine (CA) responses to amphetamine (AMPH) and phenylethylamine (PEA) were also characterized electrochemically using an in vivo model. Results of this investigation show that at a lower dose (1 mg/kg), PEA had no effect on CA release. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…It is well known that β-phenylethylamine is related to catecholamine release (Mesfioui et al, 1998;Nakamura et al, 1998;Burchett and Hicks, 2006). Recently, Xie and Miller (2004) reported that β-phenylethylamine inhibited noradrenaline uptake and induced efflux of noradrenaline through trace amine-associated receptor 1, which exists in the brainstem and other brain regions, including the prefrontal cortex (Bunzow et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that β-phenylethylamine is related to catecholamine release (Mesfioui et al, 1998;Nakamura et al, 1998;Burchett and Hicks, 2006). Recently, Xie and Miller (2004) reported that β-phenylethylamine inhibited noradrenaline uptake and induced efflux of noradrenaline through trace amine-associated receptor 1, which exists in the brainstem and other brain regions, including the prefrontal cortex (Bunzow et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A main substance of MAO-B, β-phenylethylamine, exists in the brain; it is related to catecholamine release (Mesfioui et al, 1998;Nakamura et al, 1998;Burchett and Hicks, 2006). Accordingly, we also measured extracellular noradrenaline and serotonin levels after local infusion of β-phenylethylamine to the mPFC of rats.…”
Section: Consequently Mao Inhibitors Have Been Used Only Infrequentlmentioning
confidence: 99%
“…This down-regulated GAD 67 expression likewise could be compensation to presumably altered levels of GABA induced by Amph, as it was shown that the level of GABA release was increased or decreased in the nucleus accumbens and striatum of the rat after receiving acute or repeated Amph administration (Lindefors et al, 1992; Del Arco et al, 1998; Bartolletti et al, 2004). Moreover, Amph may induce alterations in dopamine, and/or other monoamine content in the layers to affect the GABA level and GAD 67 expression (Mesfiou et al, 1998; Deng et al, 2007). By contrast, our previous study found up-regulation of GAD 67 after repeated Amph treatment in the rat neocortical areas, nucleus accumbens and hippocampus (Yin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Amph is known to be an indirect catecholamine agonist, and Amph-administered animals are utilized as models for examining addiction and Amph psychosis. The Amph-induced abnormal behavior is associated with the release of dopamine and/or other monoamines in distinct brain areas, including OlfB (Seiden et al, 1993; Karler et al, 1997; Featherstone et al, 2007; Mesfiou et al, 1998; Deng et al, 2007). There was also greater down-regulation of the OlfB pCREB in KO mice produced by the Amph exposure than that of the WT mice.…”
Section: Introductionmentioning
confidence: 99%
“…Although NE fibers are sparse in the glomeruli, the fibers are concentrated in the deep portion of the glomeruli where ET somata are located (McLean et al 1989). Additionally, neurochemical studies indicate that the NE concentration in the glomerular layer is similar to that in the deeper layers (Mesfioui et al 1998;Nadi et al 1981).…”
mentioning
confidence: 98%